PERANCANGAN WEBSITE MONITORING POSYANDU UNTUK DETEKSI DINI STUNTING DAN RESIKO PENYAKIT LANSIA - Wulandari, Oca Meilika; Firmani, Eka; Krisbiantoro, Dwi (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2026)
Healthcare service management at the village level is often hindered by manual and non-integrated recording systems, which limit early detection of health risks. This study aims to design a SmartHealth Village website using the Next.js framework to digitally monitor the health status of toddlers and the elderly, employing a Research and Development (R&D) method with a Waterfall model, conducted at Posyandu Desa Teluk, Purwokerto Selatan, Banyumas. Data were collected through observation and interviews with 9 informants consisting of 3 Posyandu cadres, 3 residents, and 3 village officials. The system automates the calculation of toddlers' nutritional status (stunting) based on WHO Z-Score standards and classifies hypertension and diabetes risk in the elderly based on JNC VII and Kemenkes RI (2020) guidelines. The website provides multi-level access for admin cadres, residents, and village officials, supported by a chatbot feature as a health education assistant. Functional testing using black-box testing showed that all 11 main features ran successfully. Performance evaluation indicated that data search time decreased from ±5–10 minutes to ±2–5 seconds, report generation time decreased from ±2–3 days to ±10–15 seconds, and calculation error rate decreased from ±10% to less than 1%, demonstrating that this platform is an efficient solution for transforming village-level healthcare management into a more transparent and responsive system.